Catch-up validation study of an in vitro skin irritation test method based on an open source reconstructed epidermis (phase II). (October 2016) - Groeber, F.; Schober, L.; Schmid, F.F.; Traube, A.; Kolbus-Hernandez, S.; Daton, K.; Hoffmann, S.; Petersohn, D.; Schäfer-Korting, M.; Walles, H.; Mewes, K.R.
Abstract: To replace the Draize skin irritation assay (OECD guideline 404) several test methods based on reconstructed human epidermis (RHE) have been developed and were adopted in the OECD test guideline 439. However, all validated test methods in the guideline are linked to RHE provided by only three companies. Thus, the availability of these test models is dependent on the commercial interest of the producer. To overcome this limitation and thus to increase the accessibility of in vitro skin irritation testing, an open source reconstructed epidermis (OS-REp) was introduced. To demonstrate the capacity of the OS-REp in regulatory risk assessment, a catch-up validation study was performed. The participating laboratories used in-house generated OS-REp to assess the set of 20 reference substances according to the performance standards amending the OECD test guideline 439. Testing was performed under blinded conditions. The within-laboratory reproducibility of 87% and the inter-laboratory reproducibility of 85% prove a high reliability of irritancy testing using the OS-REp protocol. In addition, the prediction capacity was with an accuracy of 80% comparable to previous published RHE based test protocols. Taken together the results indicate that the OS-REp test method can be used as a standalone alternative skin irritation test replacing the OECD test guideline 404. Highlights: The in vitro OS-REp skin irritation test was validated completely under open source conditions. All protocols for OS-REp construction and test performance were transferred to the participating laboratories. The study partners independently constructed the OS-REp models for validation. With 90% overall sensitivity, 70% specificity and 80% accuracy the OECD performance standards were achieved.